2007
DOI: 10.1159/000101010
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Littoral Cell Angioma of the Spleen: A Case Report and Review of the Literature

Abstract: Littoral cell angioma (LCA) is a rare benign vascular tumor of the spleen with characteristic histomorphologic features. It is a unique splenic tumor which may present with abdominal pain or as an incidental finding. Case Report: In this case report, we present the case of a 34-year-old woman with multiple splenic LCA. Initially, the patient presented with abdominal pain, weakness and fatigue. After a diagnostic abdominal ultrasound, multiple hemangiomas were observed in the spleen. Computed tomography scans c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Immunohistocytologically, the tumor cells are positive for vimentin, CD31 CD68, CD21, CD8 and FVIIIrAg, while the Ki-67 index is likely to be very low (~1%), as previously described in the literature [1,3,15,20,21].…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Immunohistocytologically, the tumor cells are positive for vimentin, CD31 CD68, CD21, CD8 and FVIIIrAg, while the Ki-67 index is likely to be very low (~1%), as previously described in the literature [1,3,15,20,21].…”
mentioning
confidence: 57%
“…Atypical cells are absent, and mitotic activity is usually very low. High-field magnification typically reveals tall and plump sinuslining cells with little mitosis, and no cytologic atypia to suggest malignancy [11,[16][17][18][19][20].…”
mentioning
confidence: 99%
“…Some cases of hyperechoic littoral cell angioma have been misdiagnosed as hemangioma on sonography. 3,20,21 In our study, 2 of the 3 hypervascular lesions were full of color flow signals when the scale was 0.077 m/s. Intralesional arterial flow signals could be clearly displayed when the scale was high enough (≥0.254 m/s).…”
Section: Discussionmentioning
confidence: 48%
“…Görg et al 16 reported 2 cases and reviewed 5 additional cases of littoral cell angioma in the literature; all cases were hyperechoic, and 6 (86%) were multiple lesions. However, in 20 cases of littoral cell angioma reported in the English literature, [3][4][5][6][7][8][9][10][11][12][17][18][19][20][21][22][23][24] 10 cases (50%) were hyperechoic, 10 (50%) were hypoechoic or isoechoic, and 12 (60%) were multiple lesions. In our study, 2 patients (29%) had multiple hyperechoic lesions, and 5 (71%) had solitary hypoechoic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Desde entonces, se han notificado alrededor de 80 casos adicionales. 2,3 La presentación clínica del ACL suele variar desde ser completamente asintomática y descubierta incidentalmente, hasta presentar una constelación de signos y síntomas como distensión abdominal, síntomas constitucionales complejos, esplenomegalia e hiperesplenismo. Aunque la tomografía computarizada (TC) y el ultrasonido (US) característicos de esta neoplasia han sido bien descritos, hay una falta de especificidad en la diferenciación del tumor de otros tumores vasculares primarios esplénicos, entre ellos, hemangiomas y angiosarcomas.…”
Section: Introductionunclassified